Assessment of the Technical Objects State by the Parameters of the Vibration Signal - P. J. Brancevich; N. V. Lapitskaya; V. A. Levantsevich; D. V. Demenkovets (Цифровая трансформация)
The aim of the research presented in this work is to develop a new method for processing a vibration signal. Among the considered the main primary informative parameters of vibration signals used to assess the vibration state of rotary-type machines. An approach based on the use of decisive functions is proposed, characterized by their application in relation to both the primary informative parameters of vibration signals and the results of statistical processing of temporal trends of primary parameters. The work also provides examples of decision functions. Also presented is the combined format of the information table on the vibration state of a technical object which is used to create real decision support systems.